Analisis Ekonomi Usaha Tanaman Pangan dan Kambing Kosta di Kecamatan Carita Kabupaten Pandeglang, Banten - Supardi Rusdiana; Endang Sutedi (Buletin Peternakan, 2016)
The purpose of this research was to determine the economic analysis of crop and livestock enterprises Costa goat. The experiment was conducted in the village of Sukarame District of Pandeglang Banten Carita. Interviews to 20 farmers the agro-ecosystem crops and livestock farmer Costa goat using questionnaires. Primary data obtained from interviews at the household unit farmers. While the secondary data obtained from the relevant authorities. Data analysis processed by descriptive qualitative, quantitative and economic analysis. The results showed that the corn plants net income around IDR.559.450,-/harvest with B/C ratio of about 1.2, whereas the results of raising of Costa goat net income approximately IDR.1.810.950,-/year, or equivalent of IDR.248.550,-/month with B/C ratio of about 1.1. The amount of man power corn farming around 131.12 HOK or equivalent of IDR.1.966.800,-/year, lot of time incurred by maize farmers are turning the land and mowing, while the man power Costa goat  around 2.57 HOK or equivalent of IDR 38.550,-/year, the time used by farmers to shepherd. Agricultural of waste crops on the research site such as corn waste can be used as feed for Costa goat.